2023
DOI: 10.3389/fcimb.2023.1273813
|View full text |Cite
|
Sign up to set email alerts
|

An update on our understanding of Gram-positive bacterial membrane vesicles: discovery, functions, and applications

Yiyun Xu,
Chonghong Xie,
Yong Liu
et al.

Abstract: Extracellular vesicles (EVs) are nano-sized particles released from cells into the extracellular environment, and are separated from eukaryotic cells, bacteria, and other organisms with cellular structures. EVs alter cell communication by delivering their contents and performing various functions depending on their cargo and release into certain environments or other cells. The cell walls of Gram-positive bacteria have a thick peptidoglycan layer and were previously thought to be unable to produce EVs. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…When analyzing PDG digestion derivatives, it has been observed that some PDG chains associated with teichoic and lipoteichoic acids initiate inflammatory responses [ 64 ], suggesting that components of the bacterial cytoplasm or molecules associated with PDG may be the main mediators of pathogenicity. This idea is supported by studies that have identified (in EVs) cytotoxic molecules from B. anthracis [ 13 ], the presence of α-hemolysin from S. aureus , hyaluronate lyase from Propionibacterium acnes , or listeriolysin O from L. monocytogenes [ 66 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 84%
See 1 more Smart Citation
“…When analyzing PDG digestion derivatives, it has been observed that some PDG chains associated with teichoic and lipoteichoic acids initiate inflammatory responses [ 64 ], suggesting that components of the bacterial cytoplasm or molecules associated with PDG may be the main mediators of pathogenicity. This idea is supported by studies that have identified (in EVs) cytotoxic molecules from B. anthracis [ 13 ], the presence of α-hemolysin from S. aureus , hyaluronate lyase from Propionibacterium acnes , or listeriolysin O from L. monocytogenes [ 66 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 84%
“…Tuberculosis, a disease caused by Mycobacterium tuberculosis , is considered the most lethal disease associated with a single microorganism, making it one of the major health emergencies worldwide [ 134 , 135 ]. The growing evidence of vesiculation in Gram-negative bacteria facilitated interest in investigating vesiculation in Gram-positive bacteria [ 13 , 65 , 66 ]. It prompted the investigation of vesiculation mechanisms in M. tuberculosis , especially after Marsollier et al isolated EVs of Mycobacterium ulcerans from skin biopsies of infected mice [ 14 ].…”
Section: Extracellular Vesicles In Other Medically Important Bacteriamentioning
confidence: 99%